Epigenomic charting and functional annotation of risk loci in renal cell carcinoma - Amin H. Nassar; Sarah Abou Alaiwi; Sylvan C. Baca; Elio Adib; Rosario I. Corona; Ji-Heui Seo; Marcos A. S. Fonseca; Sandor Spisak; Talal El Zarif; Viktoria Tisza; David A. Braun; Heng Du; et al. (Nature Communications, 2023)
The epigenomic landscape of renal cell carcinoma (RCC) remains to be explored. Here, integrative epigenomic analysis of primary human RCC samples and RCC GWAS risk SNPs identifies transcription-factor specific subtypes and enrichment of risk variants in allelically-imbalanced peaks.